Kapasitas Penyerapa Air Tanah Pada Lahan Pasca Banjir : Studi Kasus Didaerah Daratan Rendah - Gea, Damai putra jaya; Zai, Eta Juniari (CV. SINAR HOWUHOWU, 2024)
This research aims to evaluate the groundwater absorption capacity of post-flood land in lowland areas. Through quantitative and qualitative approaches, this research analyzes soil physical characteristics, infiltration rates, and the impact of flooding on land productivity. Data collection was carried out at five locations that had been identified as experiencing flooding, by measuring soil texture, density and infiltration tests using a ring infiltrometer. The research results show that variations in soil texture have a significant effect on water absorption capacity, where sandy soil has a higher infiltration rate than denser soil. In addition, interviews with farmers revealed that flooding had a negative impact on land productivity, with many farmers experiencing difficulties in post-flood recovery. Effective recovery strategies are needed to increase groundwater absorption capacity and support agricultural sustainability in flood-affected areas.